Pengaruh Market Share Investasi Mura>bahah pada Usaha Mikro dan Kecil Terhadap Profitabilitas Bank Syariah Mandiri Cabang Bone - Alfian Alfian (Institut Agama Islam Negeri (IAIN) Bone, 2019)
The purpose of this study is to determine the effect of market share mura bah ah investment in micro and small businesses on the profitability of the Bank Syariah Mandiri Branch Bone. This research is a quantitative study using the census method. Data obtained through observation, questionnaires and documentation were then processed using the chi-square formula in SPSS 21 for Windows. The results showed that the market share of mura bah ah investment in micro and small businesses had a significant effect on the profitability of the Bone Branch of Bank Syariah Mandiri.